1999
DOI: 10.1021/jo982443f
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Mediated Regio- and Chemoselective Carboxylation of Alkynes in the Presence of Carbon Dioxide

Abstract: Alkynes are carboxylated in a highly regio- and chemoselective manner in the presence of Ni(cod)2, DBU, and CO2 to give the carboxylated products in good yields. The reaction was carried out under very mild conditions (CO2 1 atm, 0 °C) in the presence of a stoichiometric amount of alkynes, conjugated enynes, or diynes. The high selectivity observed in the reaction would be explained in terms of the stability and the reactivity of the intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(74 citation statements)
references
References 27 publications
3
70
0
1
Order By: Relevance
“…The reaction proceeded under mild conditions and a wide range of organozinc reagents could be used leading to β,β'-disubstituted unsaturated carboxylic acids with an excellent regioselectivity profile that goes in line with the hydrocarboxylation procedure reported by Yamamoto and Saito (Scheme 6). [36]. Notably, the authors found that heterocyclic structures were within reach by appropriately locating a tethered heteroatom on the side-chain, thus setting the stage for an intramolecular Michael addition [39,40].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction proceeded under mild conditions and a wide range of organozinc reagents could be used leading to β,β'-disubstituted unsaturated carboxylic acids with an excellent regioselectivity profile that goes in line with the hydrocarboxylation procedure reported by Yamamoto and Saito (Scheme 6). [36]. Notably, the authors found that heterocyclic structures were within reach by appropriately locating a tethered heteroatom on the side-chain, thus setting the stage for an intramolecular Michael addition [39,40].…”
Section: Methodsmentioning
confidence: 99%
“…Gibbs free energies (kcal/mol) for the coupling of CO 2 with acetylene [34] [36]. In this work, the authors disclosed the stoichiometric carboxylation of terminal alkynes with in situ formed Ni(DBU) 2 , leading to the rapid formation of β-substituted carboxylic acids with high levels of chemo-and regioselectivity (Scheme 3).…”
Section: Scheme 1 Synthesis Of Acrylic Acids Via the Intermediacy Ofmentioning
confidence: 97%
See 2 more Smart Citations
“…Much pioneering work on catalytic CO 2 chemistry was conducted around the world including the groups of Behr [22 -27], Hoberg [28 -35], Walther [36,37], and Dinjus [38 -42], as well as Inoue [43 -47], Musco [48], Yamamoto [49,50], Darensbourg [51,52], and others [53 -57]. These efforts have developed a fundamental understanding of the chemistry of metal complexes with CO 2 providing a sound basis for the rational development of catalytic transformations of this raw material.…”
Section: Reactivity Of Co 2 At Metal Centersmentioning
confidence: 99%